2003
DOI: 10.1167/iovs.02-0669
|View full text |Cite
|
Sign up to set email alerts
|

Kainate-Triggered Currents inXenopusOocytes Injected with Chick Retinal Membrane Fragments: Effect of Guanine Nucleotides

Abstract: An alternative oocyte microinjection technique to analyze the electrophysiological properties of glutamate receptors in chick retinal membranes is described. The results show the functional activity of putative AMPA-preferring receptors from chick retina and confirm, in the chick retinal model, the antagonistic behavior of guanine nucleotides toward glutamate receptors and their potential role as neuroprotective agents under excitotoxic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…This result corroborated studies from other groups, which had previously shown that the inhibitory effects of guanine nucleotides on the binding of glutamate or ionotropic glutamatergic ligands presented several inconsistencies, when compared with studies on receptors known to be coupled to their second messengers through a G-protein [6,[87][88][89][90]. Subsequent studies from our group supported the hypothesis that guanine nucleotides could antagonize the glutamatergic transmission by acting at extracellular sites located on the membrane surface [91][92][93][94].…”
Section: Insights Into the Mechanism Of Action Of Guaninebased Purinessupporting
confidence: 86%
See 1 more Smart Citation
“…This result corroborated studies from other groups, which had previously shown that the inhibitory effects of guanine nucleotides on the binding of glutamate or ionotropic glutamatergic ligands presented several inconsistencies, when compared with studies on receptors known to be coupled to their second messengers through a G-protein [6,[87][88][89][90]. Subsequent studies from our group supported the hypothesis that guanine nucleotides could antagonize the glutamatergic transmission by acting at extracellular sites located on the membrane surface [91][92][93][94].…”
Section: Insights Into the Mechanism Of Action Of Guaninebased Purinessupporting
confidence: 86%
“…It was observed that guanine nucleotides inhibited glutamatestimulated GFAP (glial fibrillary acidic protein) phosphorylation [96], glutamate (and analogs)-induced modulation of intracellular cAMP levels [97,98], kainate-stimulated lactate dehydrogenase (LDH) release [4], kainate-activated currents [94,101] and kainate-stimulated increase in Ca 2+ influx [93]. Since most excitatory synapses in the CNS have glutamate as neurotransmitter, the potential modulatory action of guanine nucleotides on the glutamatergic neurotransmission claimed attention to new investigations on their extracellular roles.…”
Section: Insights Into the Mechanism Of Action Of Guaninebased Purinesmentioning
confidence: 99%
“…By contrast, the use of KA in rodents has been widely applied for many years and, in this sense, quinoxaline derivatives (e.g. DNQX, CNQX or NBQX) have been routinely used to antagonize the deleterious effects of KA over the last two decades (Burgos et al. , 1998, 2003; Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several groups have followed this approach of the intracellular injection of plasma membranes to study foreign membrane proteins in Xenopus oocytes (reviewed in [ 12 ]). Thus, many neuroreceptors, transporters, and ion channels have been transplanted from their original cells to the oocyte membrane including: (i) nAChRs from Torpedo electroplaques [ 33 , 47 ], muscle fibers [ 48 , 49 ], brain neurons [ 50 ], and from cell lines overexpressing heterologous neuronal nAChRs [ 26 ]; (ii) gamma-aminobutyric acid receptor type A (GABA A R) from the brain synaptosomal membranes [ 15 , 26 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]; (iii) glutamate (AMPA, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid/Kainate/NMDA, N-methyl-D-aspartate) receptors [ 26 , 52 , 62 , 63 , 64 ]; (iv) voltage-activated Na + and Ca 2+ channels from the human brain [ 34 , 65 ]; (v) Cl − channels from Torpedo electroplax [ 33 , 47 ] and from human syncytiotrophoblast microvillous membranes [ 66 ]; and (vi) membrane transporters such as P-glycoprotein [ 31 ] and the Cl − transporters, KCC1 (K + –Cl − cotransporter type 1) and NKCC2 (Na + –K + –Cl − cotransporter type 2; [ 55 ]).…”
Section: Transplant Of Fully Processed Membrane Proteins To the ...mentioning
confidence: 99%